-6(x-4)-8=19-5x

Simple and best practice solution for -6(x-4)-8=19-5x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(x-4)-8=19-5x equation:



-6(x-4)-8=19-5x
We move all terms to the left:
-6(x-4)-8-(19-5x)=0
We add all the numbers together, and all the variables
-6(x-4)-(-5x+19)-8=0
We multiply parentheses
-6x-(-5x+19)+24-8=0
We get rid of parentheses
-6x+5x-19+24-8=0
We add all the numbers together, and all the variables
-1x-3=0
We move all terms containing x to the left, all other terms to the right
-x=3
x=3/-1
x=-3

See similar equations:

| 8x+21=69 | | 15x+90=90 | | -4.2+p=12.6 | | 9x+9=48x-64 | | 3x+8(2x-6)=2x+4 | | 6(x-4)-8=19-5x | | 5+2p=8 | | 23x-9-15x+2=18x-5-10x+11 | | -4(-7+8)-7x=7(x-4)-8 | | -4+11n=10n | | 7x+18x-3=5(5x+6) | | 2/p+7=19 | | 2.2x=4.8 | | -6(7a-8)=-120 | | -6(x-4)-8=19-5 | | -9m-8=1 | | 1/x-2-5/x+7=9/x^2+5x-14 | | 4n+3-2n=-13 | | -1f-20=-2f | | 2j+3j+7=7+5j | | 2x^2-14=-x^2+7 | | 4=4x-2.4x | | -2=8-2z | | 4x=27/x+3 | | 12=20-8x | | (1)/(3)x=60 | | 8c-3=20 | | 37=6r−5 | | 8x+2x+6=37 | | 2(x+2)=11+x | | 17v=8*3 | | 3(2x+1)=4x+2x+7 |

Equations solver categories